Sobre alguns conceitos semânticos fundamentais para o ensino e avaliação nos ensinos básico e secundário - Oliveira, Fátima; Silvano, Purificação; Leal, António (Revista da Associação Portuguesa de Linguística, 2019)
The main objective of this paper is to highlight the relevance of teaching, and evaluating, some semantic contents to students of elementary and secondary schools. We put forward a proposal which includes some semantic concepts that are not taught at all or are taught, but in a shallow manner. From these, we select three to illustrate some of their features whose study may be important not only to increase students awareness of their language, but also to develop students’ skills in areas such as reading and writing.